A case of pheochromocytoma associated with liver abscess and intestinal pseudo-obstruction. (December 2022) - Okazaki-Hada, Mikiko; Fukuda, Izumi; Nagaoka, Ryuta; Nagao, Mototsugu; Igarashi, Takehito; Kobayashi, Shunsuke; Oba, Takeshi; Yamaguchi, Yuji; Nagamine, Tomoko; Sugitani, Iwao; Sugihara, Hitoshi
Pheochromocytomas can present with various symptoms. Nonspecific manifestations of pheochromocytoma include intestinal pseudo-obstruction and weight loss. Here, we present a case of pheochromocytoma in which prolonged intestinal pseudo-obstruction due to excess catecholamines was one of the factors leading to the development of a liver abscess. An 18-year-old male patient with a history of status epilepticus and severe intellectual disability was transferred to our hospital for a thorough examination of fever and constipation that had lasted for 2 months. When admitted to our hospital, he had fever, and his body mass index was 9.5 kg/m 2 . Upon comprehensive examination of the patient's fever, the blood culture was found positive for Bacteroides . Computed tomography showed findings of intestinal pseudo-obstruction and a low density region in the liver that indicated a liver abscess. Imaging studies also revealed a right adrenal mass and endocrinological test showed elevated plasma norepinephrine and urine normetanephrine levels. In addition, the right adrenal mass showed uptake on 123 I-metaiodobenzylguanidine scintigraphy. These findings led to a definite diagnosis of pheochromocytoma. The patient was eventually diagnosed with a pheochromocytoma coexisting with a liver abscess. After treating the liver abscess with antibiotics and ultrasound-guided drainage, an adrenalectomy was performed. The pathological findings were consistent with pheochromocytoma. Postoperatively, the catecholamine excess normalized and intestinal pseudo-obstruction and weight loss improved. We suspected that prolonged intestinal pseudo-obstruction resulted in bacterial translocation and development of a liver abscess. To the best of our knowledge, this is the first report of a pheochromocytoma associated with a liver abscess. Moreover, the clinical presentation of this patient was unusual for pheochromocytoma, as the patient did not have typical symptoms such as hypertension or tachycardia, but rather presented with constipation, intestinal pseudo-obstruction, and weight loss. This case provides valuable insight regarding the impact of catecholamine excess on the intestinal tract and body weight.